2001
DOI: 10.1007/s00056-001-0027-8
|View full text |Cite
|
Sign up to set email alerts
|

Early Cellular Reactions in Mechanically Stimulated Gingival Connective Tissue

Abstract: The results question the role of macrophages at the early stages of gingival remodeling incident to mechanical stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Calculation of 3 H‐TdR‐labelling indices under experimental conditions identical to those of the present investigation (11) reveals that recruitment of new cells from gingival progenitor cell populations is one of the earliest cellular events of tissue remodelling, occurring far more rapidly than cell division in wounded gingiva (9). It is manifest as conspicuous proliferative bursts both in the tissue area immediately coronal to the interdental bone crest between 1–24 h, 72 h and 168 h after the onset of mechanical stimulation and in the central zone of the papillary body within 12–24 h and after 72 h of stimulation.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Calculation of 3 H‐TdR‐labelling indices under experimental conditions identical to those of the present investigation (11) reveals that recruitment of new cells from gingival progenitor cell populations is one of the earliest cellular events of tissue remodelling, occurring far more rapidly than cell division in wounded gingiva (9). It is manifest as conspicuous proliferative bursts both in the tissue area immediately coronal to the interdental bone crest between 1–24 h, 72 h and 168 h after the onset of mechanical stimulation and in the central zone of the papillary body within 12–24 h and after 72 h of stimulation.…”
Section: Discussionsupporting
confidence: 56%
“…Subjective examination revealed that in the material of the present study the bands remained in situ for 5 d followed by loss of the bands and cessation of tooth movement thereafter. As well as having the virtue of simplicity, this experimental model ensures sufficiently prolonged mechanical stimulation of the interdental gingival papilla to induce cellular reactions which may manifest themselves over the entire experimental period (11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations